Nutritional anaemia in adolescent girls: an epidemiological study - Srivastava, Anurag; Kumar, Rakesh; Sharma, Mukesh (International Journal Of Community Medicine And Public Health, 2017)
Background: Adolescents are the future generation of any country and their nutritional needs are critical for the well-being of the society. The present study was undertaken to find out the magnitude of anaemia in adolescent girls in rural areas of district Amroha, Uttar Pradesh, India and to study the socio-demographic and nutritional factors related to anaemia. Methods: This community based, cross-sectional study was conducted in among 604 unmarried adolescent girls in the age group 13-19 years using simple random sampling. A pre-tested and pre-designed schedule was used to collect the information. Chi-square test was applied to analyse data using SPSS software. Results: Out of 604 subjects, 418 (69.2%) subjects were anemic. Majority (39.7%) had mild anaemia while 28.3% had moderate anaemia and 1.2% had severe anaemia. A higher proportion (42.1%) of the anemias were aged between 13-15 years Significant associations of Anaemia was found among those belonging to the low socioeconomic status, increased family size and less parents education Conclusions: It is important to strengthen health education on the consumption of iron rich foods and proper implementation of intervention programs that would increase the hemoglobin levels among the adolescents age group through prophylaxis treatment, dietary modification and helminthes control.